Biomonitoring of arsenic, cadmium, lead, manganese and mercury in urine and hair of children living near mining and industrial areas. (April 2015) - Molina-Villalba, Isabel; Lacasaña, Marina; Rodríguez-Barranco, Miguel; Hernández, Antonio F.; Gonzalez-Alzaga, Beatriz; Aguilar-Garduño, Clemente; Gil, Fernando
Highlights: The study was conducted in an area with large industry/mining activities. Urine and hair levels of As, Cd, Hg, Mn and Pb were determined in School children. The only significant correlation between urine and hair levels was found for Hg. Cd and Hg levels were higher than in children from other European countries. Urine Cd and Hg levels between 25% and 50% of the children might represent a health risk. Abstract: Huelva (South West Spain) and its surrounding municipalities represent one of the most polluted estuaries in the world owing to the discharge of mining and industrial related pollutants in their proximity. A biomonitoring study was conducted to assess exposure to arsenic and some trace metals (cadmium, mercury, manganese and lead) in urine and scalp hair from a representative sample of children aged 6–9 years ( n  = 261). This is the only study simultaneously analyzing those five metal elements in children urine and hair. The potential contribution of gender, water consumption, residence area and body mass index on urinary and hair metal concentrations was also studied. Urine levels of cadmium and total mercury in a proportion (25–50%) of our children population living near industrial/mining areas might have an impact on health, likely due to environmental exposure to metal pollution. The only significant correlation between urine and hair levels was found for mercury. Children living near agriculture areas showed increased levels of cadmium and manganese (in urine) and arsenic (in hair). In contrast, decreased urine Hg concentrations were observed in children living near mining areas. Girls exhibited significantly higher trace metal concentrations in hair than boys. The greatest urine arsenic concentrations were found in children drinking well/spring water. Although human hair can be a useful tool for biomonitoring temporal changes in metal concentrations, levels are not correlated with those found in urine except for total mercury, thus providing additional information.